PENGARUH KOMUNIKASI PEMASARAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PEMBELI SUARA MERDEKA SEMARANG - Alya Takwarina Cahyani; Sendhang Nurseto (Universitas Diponegoro, 2019)
As time goes on, information is a major need for all walks of life that is beneficial to the world of work, school and limited information entertainment. One source of information that can be trusted with news truths and easy to obtain both online and offline is newspapers. The oldest newspaper with the largest market share in Central Java published by Semarang is the Suara Merdeka newspaper, however problems continue to emerge which causes losses such as a decrease in the number of sales and buyers from 2014 to 2018. The purpose of this study was to determine the effect of marketing communication and product quality on the satisfaction of Suara Merdeka Semarang buyers. The type of research used is explanatory research. Data collection using tools such as questionnaires and Google forms using purposive sampling techniques. The sample used was 80 respondents who had been selected with the specified criteria. The methodology used to analyze primary data in this study is to use validity, reliability, correlation coefficient, determination coefficient, simple and multiple linear regression, t test significance, and F test with the help of the IBM SPSS version 24 program. The results showed that the contribution of marketing communication to buyer satisfaction was 30.5 percent. The contribution of the influence of product quality on buyer satisfaction by 48.8%. Simultaneously the contribution of the influence of marketing communication and product quality on buyer satisfaction was 52.1%. It means that the better marketing communication and product quality, the higher the satisfaction of Suara Merdeka newspaper buyers. In addition, product quality has the greatest influence with a regression coefficient of 0.640.